Greywater reuse in the water-scarce Gulf Region - Canal Forgues, Eric (2019)
Treated wastewater has emerged in many countries as a component of the water stream and a way to supplement, primarily, landscape and agricultural irrigation. Several European and Asian states have, in addition, promoted the use of greywater in the interior of buildings. Regulations for greywater reuse are, by and large, not in place and quality standards for different types of application are in evolution. At the same time constructed wetlands as stand-Alone or as part of the wastewater treatment system have shown promise as a way to improve wastewater effluent, while upgrading ecosystem and aesthetic aspects of a site. Gulf countries, such as the United Arab Emirates (UAE) are faced with natural water scarcity, exorbitant water demands, beyond their renewable resources and desalination capacities, overloaded wastewater treatment systems that have resulted in releases of untreated wastewater in the marine environment, and increasing populations and expanded economic activities that would further accentuate existing water problems. The current article discusses these issues and, given the public reluctance in the UAE to accept interior greywater reuse, it focuses on the applicability of constructed wetlands in the Gulf region and their potential to enhance irrigation streams and landscape appeal.